(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Local community manages sustainable cultural tourism development. Kasongan tourism village as a cultural destination in Indonesia that has been attracting many visitors in the past five years. The study adopts a strong structuration theory to explore structures influencing local communities, how they interact agents of tourism, and how they contribute to the sustainability of their destination. The study aims to fill the gap in the literature on local community involvement in sustainable cultural tourism with the application of Strong Structuration Theory, which has mostly focused on the impacts of tourism on the socio, economic, and environmental aspects of the locals. The study also provides insights and recommendations for policy makers and practitioners on how to enhance local community participation and empowerment in sustainable tourism. This study adopted constructivist paradigm, with a qualitative research approach and single case research design that used purposive sampling, data were collected by involving forty (39) respondents from seven (7) different groups such as; village leaders (1), resident-artisans (potter’s maker) (10), showroom worker (4), individual shop owners (5), tourist board officers (government) (2), private tourism organization workers (2), residents (Household) (15) through data collection methods such as observation, open ended questionnaires, focused group discussion and interview collection techniques, descriptive and thematic data analysis method was employed, and ethical issues, trustworthiness and limitation of the research were highly observed.